MOTIF, MOTIVASI, DAN MANFAAT AKTIVITASPENDAKIAN GUNUNG SEBAGAI OLAHRAGA REKREASI MASYARAKAT - Faisal Adam Rahman; Agus Kristiyanto; Sugiyanto Sugiyanto (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2017)
The purposes of this research are to know motive, motivation, and benefits for climbers and for the surrounding society of the mountaineering activities in the Mount Merbabu National Park. The research was conducted in the Mount Merbabu National Park, Central Java Province. It is a qualitative research which uses phenomenological approach. Data collection techniques used in this research are observation, interview, and documentation.    Results of research Motive, Motivation, and Benefits of Mountaineering Activities of Merbabu As Sports Recreation Society summed up as follows: 1. The motive are : 1) want to take off or surfeit due to a dense except routine 2) want to be fade into the enjoyment of natural scenery 3) try something new, 4) want to be able to interact with nature, 5) as a hobby. 2. The motivation are 1) to obtain satisfaction 2) want to reach high places and see nature 3) want to get a new experience. 3. The benefits of mountaineering for climbers are: 1) trainimg physical or exercising, 2) recreation gaining pleasure, 3) revitalize the mind or refreshing, and physical relaxation, 4) closer with the God, 5) learning to live independently 6) the character building, 7) get new friends, 8) as a means of socializing. And the benefits for the surrounding society is an income enhancement. Keywords: Physical Actitivies, Sports Recreation, Mountaineering, Mount Merbabu